2005
DOI: 10.1111/j.1365-2982.2005.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term treatment with oxytocin in chronic constipation; a double blind, placebo‐controlled pilot trial

Abstract: Nasal administration of oxytocin had no significant advantage over placebo concerning an effect on constipation. However, it seems to have a positive effect on abdominal pain and discomfort and depressed mood. These findings should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 37 publications
3
65
0
1
Order By: Relevance
“…For instance oxytocin in placebo controlled trials was shown to reduce the severity of headache and colonic visceral perception in irritable bowel syndrome (Louvel et al, 1996) but produced no beneficial effect in fibromyalgia (Mameli et al, 2014) or pain in chronic constipation (Ohlsson et al, 2005). While oxytocin has been reported to reduce pain and unpleasantness in the cold pressor test and acute laser evoked thermal pain (Paloyelis et al, 2016b) other experimental pain models have not shown a clear anti-nociceptive effect (Kessner et al, 2013;Zunhammer et al, 2015).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
“…For instance oxytocin in placebo controlled trials was shown to reduce the severity of headache and colonic visceral perception in irritable bowel syndrome (Louvel et al, 1996) but produced no beneficial effect in fibromyalgia (Mameli et al, 2014) or pain in chronic constipation (Ohlsson et al, 2005). While oxytocin has been reported to reduce pain and unpleasantness in the cold pressor test and acute laser evoked thermal pain (Paloyelis et al, 2016b) other experimental pain models have not shown a clear anti-nociceptive effect (Kessner et al, 2013;Zunhammer et al, 2015).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
“…Recent studies have shown that OT function (and that of the closely related hormone vasopressin) is impaired in brain disorders associated with social dysfunction such as autism, social anxiety, stress and schizophrenia, triggering an explosion of interest in the use of OT for treatment of mental conditions 5,6 . OT receptors have also attracted attention for their role in memory 7 , breast cancer tumour growth 8 and visceral pain 9,10 . Nasal administration of OT reduces abdominal pain and discomfort in patients with chronic idiopathic constipation 9 , whereas continuous intravenous OT significantly increases thresholds for visceral perception in patients with Irritable Bowel Syndrome (IBS) 10 .…”
mentioning
confidence: 99%
“…OT receptors have also attracted attention for their role in memory 7 , breast cancer tumour growth 8 and visceral pain 9,10 . Nasal administration of OT reduces abdominal pain and discomfort in patients with chronic idiopathic constipation 9 , whereas continuous intravenous OT significantly increases thresholds for visceral perception in patients with Irritable Bowel Syndrome (IBS) 10 . The mechanisms underlying these effects remain unclear and are important to determine as chronic abdominal pain represents a major clinical problem, with IBS alone affecting B11% of the Western population 11 .…”
mentioning
confidence: 99%
“…In recent years, more evidence has indicated that OT may play a role in regulation of the gastrointestinal (GI) functions such as motility, sensation (13,18), and immune response to inflammation (4,10). Exogenous OT influences the GI motility, although the reports are diverse because of the differences of species, methods, and area of the gut (18,24).…”
mentioning
confidence: 99%